Factors Affecting the Implementation of Performance-Based Budget - Cris Kuntadi; Ema Velayati (Eduvest - Journal of Universal Studies, 2022)
Previous or relevant research is very important in a research or scientific article writing. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence performance-based budget implementation, namely: Organizational Commitment, Resources and Rewards and Sanctions, a literature study of State Financial Management. The purpose of writing this article is to build hypotheses of influence between variables to be used in further research. The results of this literature review article are: 1) Organizational Commitment affects the implementation of performance-based budgeting; 2) Resources affect performance-based budget implementation; and 3) Rewards and Punishment affect performance-based budget implementation